RESILIENT AND BIOCLIMATIC DESIGN STRATEGIES IN BALINESE ARCHITECTURE FOR SUSTAINABLE DEVELOPMENT - Arya Bagus Mahadwijati Wijaatmaja; Putu Gde Ery Suardana; I Made Agus Eka Mahardika; Putu Gede Darmadi (International Conference on Multidisciplinary Research Perspective, 2025)
Balinese architecture reflects a harmonious integration between local wisdom, ecological adaptation, and cultural resilience. This paper explores how traditional and contemporary Balinese architectural approaches utilize bioclimatic design strategies to address challenges of sustainable development in the context of Bali. Key principles such as building orientation, natural ventilation, material selection, and spatial zoning—rooted in Tri Hita Karana and Asta Kosala-Kosali philosophies—not only ensure thermal comfort and energy efficiency but also strengthen the local identity and resilience of Balinese communities. Through multidisciplinary analysis, the study highlights the adaptation of vernacular techniques with modern innovations, demonstrating how resilient and bioclimatic architecture contributes significantly to several Sustainable Development Goals (SDGs), including climate action, sustainable cities, and cultural preservation. This approach offers a valuable model for regions facing rapid urbanization and environmental changes, affirming that sustainable architecture must embrace both tradition and innovation to achieve long-term resilience and ecological harmony.